Are Christians Mormon? - Paulsen, David L. (Routledge, Taylor & Francis Group, 2017)
"In the past, scholars and others have asked whether Mormons are Christian. This work reverses this question by asking, 'are Christians Mormon?'. By identifying Mormon doctrines formerly considered heretical and documenting how these doctrines have recently gained increasing acceptance within mainstream Christian theologies, the work presents some surprising insights. In chapters focusing on subjects such as deification, the divine feminine, and the reopening of the scriptural canon, among others, the book sets out Joseph Smith's teachings on these ideas, summarizes traditional Christian views and criticisms of Joseph's positions, and examines trends in contemporary Christian theology that significantly converge in Joseph's direction. Exploring the convergence of contemporary Christian theology with Mormon doctrines, this book will appeal to a broad range of students and other readers exploring Christian theology and Mormonism."--Provided by the publisher